Preparation and properties of metal textured polypropylene composites with low odor and low VOC - Liu Xiao-lin; Zhou Lei; Chen Jian (Science and Engineering of Composite Materials, 2020)
The aim of the present work is to upgrade the functionality and environmental friendliness of polypropylene (PP) by means of a blending technique. The influence of the metal pigment on the odor, volatile organic compounds (VOC) and metal texture of PP, and the effects of the extractant, adsorbent and processing technology on the odor and VOC of PP composites were studied systematically. It was found that metallic pigment significantly increased the VOC, odor, metallic texture and MFR of PP, and reduced the impact strength and elongation at break. The adsorbent and extractant can effectively reduce the VOC and odor of the PP composites. When the adsorbent and extractant contents were 0.5 and 5 wt%, respectively, the maximum reduction in the VOC and odor reached 73.6% and 1 level, respectively. When the extractant and adsorbent were used at the same time, the method of adding extractant and adsorbent from the main and the secondary feeding port respectively was significantly superior to the method of adding the extractant and adsorbent from the main feeding port together in reducing the odor and VOC of PP composites, which displayed a good synergistic effect.